FAKTOR PENDORONG PEMANFAATAN LAYANAN VOLUNTARY COUNSELING AND TESTING (VCT) DI PUSKESMAS - Waru, Hamsia L.; Illustri, Illustri; Sundari, Sri; Sianipar, Kandace (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
HIV-AIDS (Human Immunodeficiency Virus and Acquired Immunodeficiency Syndrome) is a secondary immune deficiency disease that remains a global public health problem to this day. Based on document searches, it is known that the use of Voluntary Counseling and Testing (VCT) services at the Jumpandang Baru Community Health Center, especially among people who are part of key populations at risk for HIV-AIDS, remains a concern. The low utilization of VCT services is feared to contribute to an increase in the incidence of HIV-AIDS. The purpose of this study was to determine the factors that encourage the utilization of Voluntary Counseling and Testing (VCT) services at health centers. A cross-sectional design was used in this study. The research was conducted at the Jumpandang Community Health Center. The population in this study consisted of all at-risk patients who visited the VCT service. The sample consisted of 55 respondents. The sampling technique used was purposive sampling. The research instrument used was a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed that there was a relationship between knowledge (p value: 0.034) and no relationship between health worker support (p value: 0.065) and the use of VCT services. It is recommended that community health centers increase cross-sector cooperation with health institutions and NGOs to organize activities that directly involve HIV/AIDS risk groups as an effort to increase knowledge and can be implemented continuously. Keywords: HIV, Knowledge, VCT